Peran Pegawai Pencatat Nikah (PPN) Dalam Mencegah Perkawinan Di Bawah Umur Di Kecamatan Jambi Selatan Kota Jambi - Balqis Salsabila, Fadhilah; Amin Qodri, Muhammad; Muhammad Daud Abdul Kadir, Sulhi (Universitas Jambi, Fakultas Hukum, 2024)
Child marriage is a marriage conducted by prospective brides and grooms who have not yet reached the age limit set by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage, which is 19 years for both men and women. In order for marriage to be achieved, underage marriages must be prevented through the role played by Marriage Registration Officers. (PPN). This research aims to identify the factors causing underage marriages in the South Jambi District of Jambi City and the role of Marriage Registration Officers (PPN) in preventing underage marriages in the South Jambi District of Jambi City. This study is an empirical legal research. The results obtained indicate that the factors causing underage marriages are free association, premarital pregnancy, family, education, and population. The role performed by PPN is to provide guidance, socialization, and counseling. However, the role performed by PPN is still not optimal in providing understanding related to underage marriage. The guidance provided by the PPN is also less effective because it is only given to prospective brides and grooms who have already registered and are about to get married. Ideally, guidance and direction should first be provided to the prospective bride and groom before expressing the desire to marry and registering at the KUA Jambi Selatan. Even if necessary, periodically, PPN can schedule when to conduct socialization related to providing information, both directly and about the side effects of underage marriage, to couples of reproductive age or teenagers still in high school and university